Değişiklik taleplerine duyarlı ve hak taleplerini azaltacak bir proje yönetim sistemi önerisi - Temel, Betül (Fen Bilimleri Enstitüsü, 2020)
Dünya ekonomisinde büyük bir öneme sahip olan inşaat sektöründe projeler; teknolojinin ilerlemesi, proje ölçeklerinin büyümesi, tarafların çoğalması, taleplerin çeşitlenmesi ve artması gibi sebeplerden ötürü her geçen gün daha karmaşık hale gelmektedir. Bu durum, projelerin istenilen süre, kalite ve maliyette başarıyla gerçekleştirilmesini zorlaştırmış, işinde tecrübeli, projeyi yönetebilecek kabiliyette Proje Yönetim Firmalarının proje sürecine katılmalarını gerekli kılmıştır. Proje Yönetim Firmalarının bu süreçte en çok karşılaştıkları sorun ise proje boyunca çok sık oluşan iş değişikliği talepleridir. İnşaat sürecinin her evresinde yaşanması muhtemel bu iş değişikliklerinin meydana gelmesi, projenin performansını önemli ölçüde etkilemektedir. Bu sebeple, sistematik bir iş değişikliği yönetimi ve iş değişikliğini azaltacak bir proje yönetim sistemi, projenin başarısı açısından hayati bir öneme sahip olmaktadır. Bu anlamda birinci bölümde çalışmanın amaç ve kapsamı anlatılmış olup, daha önce tezin amaç ve kapsamına benzer çalışmaların yapılıp yapılmadığına dair literatür taramaları yapılmıştır. İkinci bölümde dünyadaki en yaygın proje yönetim sistemleri hakkında bilgi verilmiştir. Üçüncü bölüme gelindiğinde iş değişikliklerinin ve değişiklik taleplerinin azaltılabilmesi için öncelikli olarak meydana geliş sebepleri ve ortaya çıkması durumunda proje üzerindeki etkilerinin ne olacağı konusu araştırılmıştır. Bu anlamda yerli ve yabancı makaleler, kaynaklar, araştırmalar incelenerek dünya genelindeki inşaat projelerinde karşılaşılan bu durumun temel sebepleri, kaynakları, etkileri irdelenmiştir. Bölümün son kısmında ise iş değişikliklerinin meydana gelmesi sonrasında yönetim sisteminin ve sürecin nasıl işlediği konusu yine literatür taramasından elde edilen veriler ile anlatılmıştır. Dördüncü bölümde teze konu örnek projedeki iş artış ve azalış sebeplerinin daha iyi anlaşılabilmesi için örnek projeyi yöneten firmanın proje yönetim sistemi detaylı anlatılmış olup beşinci bölümde örnek proje hakkında genel bilgi verilmiştir. Altıncı bölümde iş artış ve azalışlarının sebepleri teze konu örnek projede yaşanan olaylar üzerinden anlatılmış ve projede yaşanan iş değişikliklerinin ve değişiklik taleplerinin proje bütçesine, süresine, iş gücü veremliliğine, taraflar arasındaki ilişkiye etkisi detaylandırılmış ve ''Örnek projedeki iş değişikliklerinin hangi noktalarda önüne geçilebilirdi?'' sorusuna cevaplar verilmiştir. Ayrıca örnek projede iş emri değişikliğinin ortaya çıkması sonrası oluşan hak talebi yönetim sürecine yönelik akış şeması oluşturulmuş, yönetim sürecinin aksayan yönleri belirtilerek hak talebi yönetim sürecinin iyileştirilmesine yönelik öneri akış şeması oluşturulmuştur. Yedinci bölümde ise literatür taramalarından ve örnek vaka analizinden elde edilen veriler ile iş artış ve azalışlarını minimize etmek için hangi proje paydaşının tasarım öncesi dönemden başlayarak, inşaatın tamamlanması sonrası dönemi de kapsayacak şekilde hangi aşamada hangi önlemi alması gerektiği tablo ile sistematik hale getirilmiş olup çalışmanın Proje Yönetim Sistemine ve inşaat sektörüne katkısından bahsedilmiştir.

Although the construction sector is one of the sector that contribute to the development of Turkey's economy and the world economy, it is one of the sectors that are most affected by internal and external movements in the economy. Along with the economic movements, geopolitical and political risks and uncertainties also cause a decrease in confidence in the construction sector. Despite the fact that the construction industry is affected by uncertain parameters and its sensitivity to the economy decreases the trust towards the sector gradually, the volume, size and complexity of the investments in the construction sector are increasing day by day. For this reason, the owners and investors need professionals who are able to predict the risks that may arise in their large and complex investments in order to create a safer environment for them in an unsafe and risky area, manage these risks, prevent or reduce them when necessary, and thus capture the time, quality and budget in their projects. The necessity of filling the gap at this point in the world, people's willingness to make construction investments in an environment that will make them feel more secure, and the demands for investments to be carried out at the desired time, quality and cost have made it inevitable for Project Management Firms to participate in the construction projects process. The most common problems encountered by the Project Management Companies in this process are the demands for changes that occur frequently throughout the project. These changes, which are likely to occur at every stage of the construction process, significantly affect the performance of the project. Therefore, a systematic change management and a project management system that will reduce changes are vital to the success of the project. Considering the existing Project Management Systems in this regard, especially while they remain insufficient to reduce changes in the construction sector in Turkey. In this master's thesis, in order to fill the gap in this regard, it has been made systematic with the table which is including which project stakeholder, at what stage, and what action to take starting from the pre-design period to after the completion of the construction, in order to reduce the demands of work order changes during construction projects. If the subject of the thesis study is explained in more detail according to the departments, after the subject of the study is explained in general; In the first part, many domestic and foreign sources and studies have been examined and a literature review has been made in order to get detailed information and to find out whether similar studies have been carried out on the main subject of the thesis. The results of the literature on change orders and change order management system in Turkey were found to be too much work for the reduction of changes. Able to obtain information about change management systems from their sites numbered Project Management Company located in Turkey on the issue. When international studies and sources are analyzed, it is seen that many researches and studies have been done about the causes, effects and how to manage the change orders that occur in the project processes in the construction sector. In the researches, it has been determined that the studies carried out to minimize the work changes in the construction sector are not in the scope and detail that can reduce the work change, but only at the level of recommendation. In addition, since it is aimed to introduce a comprehensive system proposal for reducing the work change in the sample project subject to the thesis, every phase of the project process has to be examined in detail, and the reasons that may cause the work change for each phase of the project have been tried to be determined. In the second part, information is given about the most common project management systems in the world. In order to minimize the frequent changes in the construction industry, the reasons for their emergence and their impact on the project must be well known. Because, if the reasons for emergence can be eliminated or the effect on the project can be reduced after its emergence, then the project will only achieve the desired success. With this perspective, in the third part, the main causes, sources and effects of this situation encountered in construction projects around the world are examined by investigated the domestic and foreign articles, sources and researches. Survey studies and researches on this subject in the World Show that there are many reasons for job change, the main ones are; financial problems of Owner, instabilities in designs, requests or Owner for revisions and Owner delays in decision making, and missing and errors in designs, incompatibilities between contract and contract projects, errors in strategic planning, and Contractor's inability to do the job. As a result of the researches, the biggest impact of changes was on the project budget, project duration, labor productivity and bilateral relations between the project parties. In the last part of the chapter, the issue of how the management system of the change orders and the process of changes after the occurrence of change orders is again explained with the data obtained from the literature review. After investigating the causes and effects of changes through the literature review, in the second stage of the thesis, data on the causes and effects of changes were tried to be obtained through the sample project, where the author previously worked and changes were abundant. Before explaining the causes and effects of the changes in the sample project, which is the subject of the thesis, it is necessary to know the process, the management system and the general structures of the project participants in order to better understand the causes of the changes. For this reason, in the fourth chapter, the phases involving the Project Management Firm managing the project are mentioned in order to show how the exemplary project subject to the thesis goes through the processes. These processes, which are the general management style of the Project Management Firm, are explained in detail and supported with documents and documents. Again, in order to better understand the changes in the sample project subject to the thesis, in the fifth chapter, general information about the project is given and the structure and participants of the projects which are Owner, Contractor, Project Management Firm and Design Groups are mentioned. In the sixth chapter, the reasons for the increases and decreases of the works are explained through the events experienced in the sample project subject to the thesis. In the sample project, more than 100 changes and change orders have occurred, 15 of them have been analyzed and the reason for the occurrence, who originated, how it was evaluated after emergence, and finally what the effects on the project have been explained in detail. Afterwards, the effects of changes and change orders on the project budget, duration, labor productivity and relations between the parties are explained in detail. Although it is not possible to provide detailed information due to the confidentiality agreement of the sample project that is the subject of the thesis, ıt has been identified that the changes experienced in the sample project and approved at the end of the project are originated 65% from Owner, 25% from Project Management Firm and Design Group and 10% from Contractor. According to the results obtained, although the Contractor seems to cause less changes than others, the unfair demands he/she conveyed during the project caused tensions among the project participants, the project's motivation decreased and consequently caused losses that were not seen directly. When analyzed by work item, it is seen that the budget increase due to changes are 31% of due to architectural and construction works, 40% is due to electrical works and 29% is due to mechanical works. Since it is very important to manage successfully in case of occurrence as well as preventing the occurrence of changes, the management system of change order that emerged in the project was explained and a flow chart was created for the claim management process. In the last part of the section, the disruptive aspects of the changes and claim management process in the project are specified and a suggestion flow chart is developed for the improvement of the claim management process. As a result, the data obtained from all the examples described are categorized as to why the Owner, the Contractor and the Consultant caused the changes. In the conclusion part, with the data obtained as a result of detailed literature scans and sample case analyzes, it is systematic with the table which is including which project stakeholder, at what stage, and what action to take starting from the pre-design period to after the completion of the construction, in order to reduce the demands of work order changes during construction projects. When this detailed table is analyzed, it is seen that the actions to be taken to reduce changes in project are compatible with the "Integrated Project Management System". When we look at the working and target principles of the Integrated Project Management System, it is clearly seen that less demand for changes will occur in the projects started with this management system compared to the projects managed by the Traditional Management System. However, the Integrated Project Management System working process is until the end of the construction phase and does not carry out any work for the users to solve the problems they encounter in the post-construction process. Contrary to the Integrated Project Management System, works continue in the post-construction phase, and it is aimed to deliver safe, comfortable and high-quality projects for customers in the table study, in which aiming at the writing of the thesis and aiming at the reduction of changes and change orders are taken and systematized, Whether it is in a wide range and in detail including from pre-design phase to post-design phase, and analyzing it by making detailed analysis on the real events that the author is in, ıt is clear how great the solution will be to the problems in the literature and the sector. In summary, according to the information obtained from the literature surveys, it is not possible to complete the project without changing the construction projects. For this reason, in this thesis, it is aimed to minimize the changes and change orders that occur during the construction projects instead of eliminating them; From the pre-design period to the period after the completion of the construction, which project stakeholder, at what stage, and what action to take has been made systematic with the table. In this study, aimed the reduction of changes and change orders experienced in construction projects in Turkey and to fill the gap in this field in Turkey also. It is thought that this study will also contribute to the Integrated Project Management System on the work to be carried out in the "post-production" process.
Recommendation of project management system to reduce change order with integrated project management system
Keywords: Anahtar teslimi inşaat sözleşmesi; Turnkey construction contracts; Organizational project management; Organizasyonel proje yönetimi